PRIBADI DIPATI UKUR PAHLAWAN TATAR SUNDA - Zaenal Hakim (Sawo Manila, 2010)
Carita Dipati Ukur is a script concerning about a death myth of Dipati Ukur that people said his head was cut off by a king of Mataram in Java. According to this script, that man was not the real Dipati Ukur, but Raden Wangsanata who admitted as Dipati Ukur. By using reception theory, we must regard this script as a literature which must be understood as a dialogue creation, and the philosophic expertise has to be built in rereading the text continuously, while it is not only about the facts. Carita Dipati Ukur by Rohendy and Supis (1959-1960) was the answer of the unsatisfactory of Sundanese towards those temporary verses of CDU script written but in negative impression through the character of Dipati Ukur.